Cognitive impairment in PSP compared with PD: assessment by clinical subtype and longitudinal change - Ikuko Aiba; Hiroshi Tatsumi; Rina Hashimoto; Takeharu Tsuboi; Kosuke Kobayasi (BMJ Neurology Open)
Background Longitudinal studies investigating cognitive function changes in patients with progressive supranuclear palsy (PSP) are limited. The variability of cognitive impairment across clinical subtypes of PSP remains unclear.Objective This study aimed to compare the longitudinal changes in cognitive function between patients with PSP and Parkinson’s disease (PD) and to assess differences in cognitive impairment among PSP subtypes.Methods A retrospective observational study was conducted using neuropsychological testing data from patients with PSP and PD admitted to our hospital.Results The study included 38 patients with PD and 41 patients with PSP (23 PSP-Richardson’s syndrome, 14 PSP-progressive gait freezing (PSP-PGF), 3 PSP-Parkinsonism and 1 PSP-predominant corticobasal syndrome). At baseline, cognitive function was significantly lower in the PSP group than in the PD group. Over 12 months, patients with PSP exhibited significant declines in multiple cognitive domains, whereas no significant changes were observed in the PD group. Among PSP subtypes, PSP-RS showed a faster rate of cognitive decline than PD, while PSP-PGF demonstrated a lower progression than PSP-RS.Conclusion PSP is associated with progressive cognitive impairment, with rates of decline varying by subtype. PSP-PGF exhibited a slower progression than PSP-RS. Clinical management should consider subtype-specific differences in cognitive prognosis to tailor treatment and care.